Biofilm-Based Immobilization Fermentation for Continuous hEGF Production in Saccharomyces cerevisiae - Kaiqi Zhi; Zhiguo An; Mingyang Zhang; Kehan Liu; Yafan Cai; Zhenyu Wang; Di Zhang; Jinle Liu; Zhi Wang; Chenjie Zhu; Dong Liu; Sheng Yang; et al. (Fermentation)
Biofilms can enhance industrial fermentation efficiency by increasing cell density, stability, and metabolic activity and have been successfully applied to the continuous production of many small-molecule chemicals. However, the continuous production of proteins by biofilms has been less studied. This study used secretory human epidermal growth factor (hEGF) as a representative product to evaluate and optimize biofilm-based continuous protein production. First, by deleting the protease and overexpressing eight key genes involved in protein secretion in Saccharomyces cerevisiae, the yield of hEGF was improved by 82.6% from 77.4 to 141.3 mg/L in shake flasks. Subsequently, the flocculation genes FLO11 and ALS3 were introduced to facilitate the establishment of a biofilm-based continuous immobilization fermentation model. The optimal strain SIC-ALS3-PDI1 produced 583.8 mg/L of hEGF, with a productivity of 4.9 mg/L/h during traditional free-cell fermentation, while it produced an average of 300.0 mg/L of hEGF in 10 continuous batches of biofilm-based fermentation, with a productivity of 6.3 mg/L/h. Although the hEGF production in biofilms was lower than that in free-cell fermentation, biofilm fermentation demonstrated greater productivity, with the advantage of not requiring seed culture for each batch of fermentation. This study provided a valuable reference for the biofilm-based production of other peptides.